Contemporary Ijtihad on Online Lending Practices: An Analysis of Sharia Business Ethics Based on the Principle of La Darara Wa La Dhirara - Nurfauzan, Abdul Nafi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Analyzing the practice of Online Loans (Pinjol) from the perspective of Islamic business ethics with a focus on the Main Principle of Usul Fiqh: Lā Ḍarara Wa Lā Ḍirāra (should not harm oneself or others). This study aims to identify the elements of harm (ḍarar) caused by Pinjol and formulate a binding contemporary ijtihad (Ilzāmiy) regarding its legality. Methodology: This research uses a normative legal research method. Results: This study shows that online lending (pinjol) causes extensive multidimensional harm, including: Financial exploitation: High interest rates that resemble riba (usury). Psychological/social impacts: Aggressive debt collection that violates the protection of life (hifẓ al-nafs). Informational harm: Personal data leaks. The principle of "Lā Ḍarara Wa Lā Ḍirāra" (the principle of "lawfulness and justice") is implemented as an ethical criterion through three functions: Hadhr (limiting maximum interest rates), Ibti'ād (preventing consumer harm), and Tawāzun (balancing profits). Based on their intensity, contemporary ijtihad recommends that online lending practices with "darar fāḥish" (large losses) are haram. Applications/Originality/Value: Offering constructive solutions in the form of developing alternative models of Islamic financing free from ḍarar, such as Qardhul Hasan or Murābaḥah. This is an effort to achieve social welfare (Taḥqīq Maṣāliḥ) through strict regulations and Islamic ethics in the digital financial ecosystem.